KAJIAN ANALISIS KETIDAKPASTIAN TLD POSTAL IAEA/WHO SEBAGAI STANDAR PROGRAM AUDIT DOSIS - Nazaroh Nazaroh (Badan Standardisasi Nasional, 2009)
The International Atomic Energy Agency (IAEA) and World Health Organization (WHO) operate the IAEA/WHO TLD postal dose audit programme using thermoluminescence dosimeter (TLDs) for Secondary StandardDosimetry Laboratory (SSDL) and user every year. As National Reference Laboratory in the field of radiation metrology, PTKMR – BATAN always participates in the postal dose audit programme on therapy level for 60Cobeam. On the postal dose audit programme, the uncertainties in the dose determination from TLD measurements have been evaluated by IAEA, which is comprises of uncertainties in the calibration coefficient of the TLD systemand uncertainties in factors correcting for dose response non linearity, fading of TL signal, energy response, and influence of TLD holder. The individual uncertainties then have been combined to estimate the total uncertaintiy inthe dose evaluated from TLD measurements. The combined relative standard uncertainty in the dose determined from TLD measurements has been estimated to be 1.2% for irradiation with 60Co gamma rays and 1.6% forirradiation with high-energy X-rays. Results from irradiations by Bureau Internationale des Poids et Mesures (BIPM), Primary Standard Dosimetry Laboratory (PSDL), and SSDL compare favourably with the estimateduncertainties, whereas TLD results of radiotherapy centres show higher standard deviations than those derived theoretically. This paper presented the result of TLD postal dose audit for 60Co beam owned by PTKMR-BATANin the year of 2006-2008.